STRATEGY OF IMPLEMENTING MERIT SYSTEM AT INSPECTORATE OF DKI JAKARTA PROVINCE - Yudo Ariyono Priyadi (DIA: Jurnal Administrasi Publik, 2026)
The implementation of a merit system is a crucial component in enhancing the professionalism and competency of civil servants within government institutions. This study explores the strategy for applying the merit system within the Inspectorate of the Special Capital Region (DKI) Jakarta Province. The research is driven by the gap between regulatory mandates and the actual application of merit principles in staffing processes, such as recruitment, promotion, and placement, which often remain inconsistent with employee competencies. Using a qualitative descriptive approach, the study collects data through interviews, observation, and document analysis involving key informants from the DKI Jakarta Inspectorate and related agencies. The findings reveal that although legal frameworks and policies supporting meritocracy are already in place, such as the Peraturan Gubernur No. 8 Tahun 2022 and the Keputusan Gubernur No. 120 Tahun 2022, several challenges persist. These include insufficient talent management practices, lack of transparency, limited public oversight, and internal resistance to change. The study proposes strategic recommendations to optimize the merit system, emphasizing competency-based human resource management, enhanced supervision, talent pool development, and institutional capacity building. The results are expected to provide insights for public HR policy formulation and serve as a reference for improving bureaucratic performance through merit-based governance.